Respuestas

2013-12-18T01:44:02+01:00
(3/5 + (7/2 - 1/3) ÷ (19/12)) = (3/5 + (21/6 - 2/6) ÷ (19/12)) = (3/5 + (19/6) ÷ (19/12))
= (3/5 + (38/12) ÷ (19/12)) = (3/5 + 2 ) = 2 \frac{3}{5}

(20*((7/8 + 3/2) ÷ (19/16))) = 20 *( (7/8 + 12/8) ÷ (19/16)) = 20 * ((19/8) ÷ (19/16))
= 20* ( 38/16 ÷ 19/16 ) = 20*2 = 40

( 2/5 + ((1/4 ÷ 7/16)* ( 21/2)) - 3) = 2/5 + ((4/16 ÷ 7/16) * 21/2) - 3 = 2/5 + (4/7 * 21/2 ) - 3
= 2/5 + (6) - 3 = 2/5 + 3 = 3 \frac{2}{5}

(3 + ((3÷ 3/4)* 1/2 + 5)) = 3 + ((12/4 ÷ 3/4) * 1/2 + 5) = 3 + (3*1/2 + 5) = 3 + (3/2 + 10/2)
= 3 + 13/2 = 19/2 = 9 \frac{1}{2} 

(21/3 * (1/2 - 1/3)) = 21/3 * (3/6 - 2/6 ) = 21/3 * 1/6 = 21/18 = 7/6 = 1 \frac{1}{6}

Si son 900 alumnos, 2/3 de los alumnos son :
900 * 2/3 = 300 * 2 = 600 alumnos tienen menos de 10 años